Existential Social Work in Coping with Death and Grief - Temiz, Rıdvan; Temiz, Rıdvan (Springer, 2025)
This article delves into the use of existential social work in coping with death and grief. After defining death and grief, the article explores individuals' attitudes towards death and the theoretical perspectives related to death and grief. The article further examines the fundamental concept of existentialism within the context of coping with death and grief. The article then considers the theoretical basis of an existentialist approach to social work evaluation and intervention. It highlights the importance of an existentialist approach in the process of coping with death and grief, as it encourages individuals to confront the reality of death and find meaning in life. Ultimately, the article contributes to the field of social work by providing insights into the theoretical foundations of existential social work in the context of death and grief. In order to enhance understanding, this article includes a case example, contributing to a deeper understanding of the practical application of existential social work in dealing with death and grief.
Keywords: Death; Grief; Existentialism; Existential Social Work